What Works for Whom, How and under What Circumstances? Testing Moderated Mediation of Intervention Effects on Externalizing Behavior in Children. Issue 2 (11th March 2013) - Stoltz, Sabine; Deković, Maja; van, Monique; Orobio de Castro, Bram; Prinzie, Peter
Abstract In this study, we investigate whether changes in child social cognitive functioning and parenting are the mechanisms through which an individually delivered real‐world child intervention, Stay Cool Kids, aimed at preventing externalizing problem behavior in high‐risk elementary school children, induces changes in child behavior. Moreover, we tested whether mediation was moderated by child characteristics (gender and personality). The sample consisted of 264 fourth‐grade children displaying externalizing behavior (TRF t‐score > 60). Forty‐eight schools were randomly assigned to the intervention or no‐intervention control condition. The results of mediation analyses provided evidence for child positive self‐perception and maternal involvement as working mechanisms of the intervention. Child personality factor extraversion moderated the mediating effect of involvement whereas no moderated mediation was found for gender. Working mechanisms of the intervention differ for children with different personality characteristiscs.